Deployment of Smart Pipeline Tie-Ins Technologies on Jazan Abha Pipeline Project (JAPP) - Savio, Rajesh D; Alhaji, Mohammed H (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
Pipeline technologies have significantly improved project execution by providing smart tools to address constraint’s and improve the project cost and schedule. The Jazan Abha Pipeline Project (JAPL-2) aimed to develop oil supplies to the southern region of Saudi Arabia by constructing and upgrading pipelines over more than 90 km of challenging terrain. This paper discusses the state-of-the-art advancements utilized to complete joint activities in the JAPL-2 project connected with the existing JAPL-1 pipeline. Key challenges included creating connections in remote areas and steep inclines, requiring precise regulation to minimize closure times and avoid extensive downtime. The approach incorporated advancements from Remote Techno Plug (RTP) and BISEP, along with engineered supports, to provide robust pipeline separation and reduced downtime. These developments facilitated double block and bleed isolation, remote-controlled operations, and consistent hot tapping, ensuring safe and efficient transitions. The implementation framework included two four-day closure periods to connect tie-ins at Booster Stations (BS1) and (BS2). This approach minimized operational interruptions, enhanced safety by reducing manual task loads, and improved resource usage. The team obtained necessary approvals, conducted an in-depth review, and implemented the plan. High-level advancements in key separation and integration were important in overcoming project challenges, resulting in reduced downtime, improved safety, and consistent standard operations. The outcome concluded a successful story by accomplishing the required job safely and proving the team’s effort in strategizing the execution by selecting the most appropriate and advanced technologies.